Efektivitas Senam Hamil terhadap Penurunan Nyeri Punggung pada Kehamilan Trimester III di RSUD Ciawi - Ermawati Destri Nurlitawati; Yenny Aulya; Retno Widowati (Jurnal Akademika Baiturrahim Jambi, 2022)
Pain in the lower back is a common musculoskeletal problem during pregnancy with the prevalence of pregnant women in Indonesia being 4.8%, while for West Java it is 5.3%. One way to improve health during pregnancy is to do light exercise such as pregnancy exercise. Pregnancy exercise is able to release endorphins in the body, where the function of endorphins is as a sedative and can reduce back pain in pregnant women. This study aims to determine the effectiveness of pregnancy exercise on reducing back pain in third trimester pregnant women at Ciawi Hospital. This quasi-experimental study used a one group pretest and posttest design. The population totaling 20 respondents. The instrument used in this study was the Wong Baker FACES Rating Scale for pain measurement. Pregnancy exercise is done for 1 month to reduce back pain in pregnant women. From the results of the study, a significant value of paired sample t-test was obtained, a significant value of 0.002 < 0.05, meaning that there was a change in back pain in third trimester pregnant women at Ciawi Hospital in 2021 before and after pregnancy exercise. There are significant results on changes in pain in back pain in third trimester pregnant women at Ciawi Hospital in 2021 before and after pregnancy exercise. It is hoped that health workers, especially midwives, can work together to increase education about back pain and the benefits of pregnancy exercise, so that pregnant women have awareness to do pregnancy exercise.